Vertical sleeve gastrectomy normalizes circulating glucocorticoid levels and lowers glucocorticoid action tissue-selectively in mice - Akalestou, Elina; Lopez-Noriega, Livia; Christakis, Ioannis; Hu, Ming; Miras, Alexander D.; Leclerc, Isabelle; Rutter, Guy A. (Frontiers in Endocrinology, 2022)
Objectives: Glucocorticoids produced by the adrenal cortex are essential for the maintenance of metabolic homeostasis. Glucocorticoid activation is catalysed by 11β-hydroxysteroid dehydrogenase 1 (11β-HSD1). Excess glucocorticoids are associated with insulin resistance and hyperglycaemia. A small number of studies have demonstrated effects on glucocorticoid metabolism of bariatric surgery, a group of gastrointestinal procedures known to improve insulin sensitivity and secretion, which were assumed to result from weight loss. In this study, we hypothesize that a reduction in glucocorticoid action following bariatric surgery contributes to the widely observed euglycemic effects of the treatment. Methods: Glucose and insulin tolerance tests were performed at ten weeks post operatively and circulating corticosterone was measured. Liver and adipose tissues were harvested from fed mice and 11β-HSD1 levels were measured by quantitative RT-PCR or Western (immuno-) blotting, respectively. 11β-HSD1 null mice (Hsd11b1-/-) were generated using CRISPR/ Cas9 genome editing. Wild type (WT) and littermate Hsd11b1-/- mice underwent Vertical Sleeve Gastrectomy (VSG) or sham surgery. Results: WT VSG-treated mice displayed significantly improved glucose tolerance versus sham controls, and this effect was observed in both regular chow- and HFD-fed animals. VSG lowered body weight in HFD but not regular chow-fed mice. Remarkably, VSG restored physiological corticosterone production in HFD mice and reduced 11β-HSD1 expression in liver and adipose tissue post-surgery. Elimination of the 11β-HSD1/Hsd11b1 gene mimicked the effects of VSG on body weight and tolerance to 1g/kg glucose challenge. However, at 3 g/kg glucose, the impact of VSG on glucose excursion was indistinguishable between WT and Hsd11b1-/- mice, suggesting that the euglycemic effect of VSG was superior to Hsd11b1 elimination. Conclusions: Bariatric surgery improves insulin sensitivity and reduces glucocorticoid activation at the tissular level, under physiological and pathophysiological (obesity) conditions, irrespective of weight loss. These findings point towards a physiologically relevant gut-glucocorticoid axis, and suggest that lowered glucocorticoid exposure may represent an additional contribution to the health benefits of bariatric surgery.